Analisis Kelayakan Usahatani Jamur Tiram Putih di Kursus Pertanian Taman Tani (KPTT) Kota Salatiga - Cynthia, Monika Mei; Nuswantara, Bayu (Universitas Galuh, 2024)
This research aims to determine the magnitude of production costs, revenues and farming income, analyze the feasibility of farming from an economic perspective, and analyze the sensitivity of white oyster mushroom farming in KPTT Salatiga City. The research was conducted from July to August 2023. This type of research is quantitative descriptive by calculating total production costs, revenues and farming income, analyzing revenue cost ratio (R/C ratio), benefit cost ratio (B/C ratio), break even point (BEP), as well as sensitivity analysis. The data in this research was taken when farming conditions tended to be stable, namely from April 2022 to March 2023. Data collection was carried out using observation, interviews and documentation methods. The research results show: 1). Production costs incurred amounted to IDR 63,865,850, with receipts of IDR 79,903,225, resulting in income of IDR 16,037,375. 2). The R/C ratio value is 1.25; B/C ratio value of 0.25; BEP production of white oyster mushrooms was 4,913 units; The BEP price for white oyster mushrooms is IDR 12,939/kg. 3.) The highest simulated R/C ratio and B/C ratio values occur when production and selling prices increase 10% simultaneously with R/C ratio values of 1.51 and B/C ratio 0.51, while the experimental simulation of R/ The lowest C ratio and B/C ratio occurred when production costs increased by 20% with an R/C ratio of 1.06 and a B/C ratio of 0.06.